THE EFFECTS OF ORGANIZATIONAL JUSTICE AND CONSCIENTIOUSNESS ON CYBERLOAFING (Third Sector Social Economic Review, 2020)
The main purpose of this study is to research the effects of the organizational justice perception and conscientiousness of the employees on their cyberloafing behavior. Dataset of the study consists of total 232 questionnaires gathered from the employees working at the central organization of the general directorate of a government agency in Ankara. Data input and analyses were done with SPSS software. Validity, reliability, Pearson correlation, and simple linear regression analyses were employed in this study. According to the analysis results in this study, significant relationships between perceived organizational justice and its sub-dimensions, and cyberloafing were not revealed. However, employees’ conscientiousness affects their cyberloafing behavior in a significant and negative way. It is concluded that it is possible to decrease the damage caused by cyberloafing to the organization and thus to contribute to the organization through the mitigating effects of increased level of employees’ conscientiousness on their cyberloafing behavior.
Keywords: Cyberloafing; Organizational Justice; Conscientiousness.